Geographical and environmental dimensions of health conditions affecting population deaths in Libya for the period 2016-2017: Study in Population Geography (Journal of Academic Research, 2021)
The study of mortality is the basis for determining the growth and size of the population, age, gender and other structures. This study aims to research the analysis of geographical dimensions affecting deaths in Libya during the years 2016-2017. The study focused on the role of geographical factors, especially climatic and environmental factors that cause diseases in addition to the ten causes. The first major death, which varies greatly between the population of one country and another and between one time and another, and is subject to various factors, including health and environmental conditions. Where the study found that climatic factors, especially heat, which was a major cause of the spread of many diseases such as cardiovascular disease, influenza, chest diseases, high blood pressure, which are among the main causes of death at all ages of both sexes, as well as environmental factors represented in air pollution caused Factories and garbage dumps near residential communities play a helpful role in the spread of neoplastic and kidney diseases that often lead to death.